EDUKASI DAMPAK SAMPAH PLASTIK TERHADAP LINGKUNGAN LAUT BAGI SISWA SEKOLAH DASAR NEGERI 6 MEULABOH ACEH BARAT - Dini Islama; Mai Suriani; Nurul Najmi; Mira Mauliza Rahmi; Citra Dina Febrina; Fitria Rahmayanti (Universitas Teuku Umar, 2021)
Plastic waste in the sea is a global problem that directly harms the marine environment (damaging marine ecosystems and threatening the lives of marine organisms), and can indirectly interfere with human health and life. This activity aims to provide knowledge to students at State Elementary School 6 Meulaboh West Aceh about the impact of plastic waste on the marine environment and human life indirectly, as well as instilling an awareness of the importance of keeping the sea clean from an early age. This activity was carried out using the lecture method and interactive discussion with the students of State Elementary School 6 Meulaboh West Aceh. The output of this activity is to increase the awareness of elementary school students about the importance of keeping the marine environment clean and not littering. At the end of the activity, the distribution of tumblers and trash cans was carried out to minimize the use of plastic and provide a garbage disposal container at State Elementary School 6 Meulaboh. With this educational activity, students have been provided with knowledge from an early age about the importance of keeping the marine environment clean from plastic waste, so that in students there is a passion not to throw garbage into the sea or that ends up in the sea because of the large environmental impact that will arise if the polluted sea.